The validity of a four week self-recall of sports injuries. Issue 3 (2nd June 2005) - Valuri, G; Stevenson, M; Finch, C; Hamer, P; Elliott, B
Abstract : The ability of sports injury studies to provide reliable incidence estimates depends on accurate injury data. One of the most commonly used methods of collecting injury data is through self-report, but the validity of such information is largely unknown. This study validated a four week self-report sports injury recall against a range of external sources including hospital records, health practitioner records, and third parties. Cases were drawn from the larger, Western Australian Sports Injury Study (WASIS). This study demonstrates acceptable to good levels of agreement between self-report and more objective data in relation to details such as the nature and body part injured, and the level of injury treatment sought (κ = 0.48 to 0.78). However, self-reported injury severity did not agree with the Injury Severity Score classification of severity.